A Standardized Strategy for Simultaneous Quantification of Urine Metabolites to Validate Development of a Biomarker Panel Allowing Comprehensive Assessment of Dietary Exposure. Issue 20 (28th September 2020) - Beckmann, Manfred; Wilson, Thomas; Zubair, Hassan; Lloyd, Amanda J.; Lyons, Laura; Phillips, Helen; Tailliart, Kathleen; Gregory, Nicholas; Thatcher, Rhys; Garcia‐Perez, Isabel; Frost, Gary; Mathers, John M.; et al.
Abstract : Scope: Metabolites derived from individual foods found in human biofluids after consumption could provide objective measures of dietary intake. For comprehensive dietary assessment, quantification methods would need to manage the structurally diverse mixture of target metabolites present at wide concentration ranges. Methods and results: A strategy for selection of candidate dietary exposure biomarkers is developed. An analytical method for 62 food biomarkers is validated by extensive analysis of chromatographic and ionization behavior characteristics using triple quadrupole mass spectrometry. Urine samples from two food intervention studies are used: a controlled, inpatient study ( n = 19) and a free‐living study where individuals ( n = 15) are provided with food as a series of menu plans. As proof‐of‐principle, it is demonstrated that the biomarker panel could discriminate between menu plans by detecting distinctive changes in the concentration in urine of targeted metabolites. Quantitative relationships between four biomarker concentrations in urine and dietary intake are shown. Conclusion: Design concepts for an analytical strategy are demonstrated, allowing simultaneous quantification of a comprehensive panel of chemically‐diverse biomarkers of a wide range of commonly‐consumed foods. It is proposed that integration of self‐reported dietary recording tools with biomarker approaches will provide more robust assessment of dietary exposure. Abstract : Limit of detection, limit of quantification, and summary of concentration ranges of dietary biomarkers in urine collected from free‐living individuals.